Idioms Between Arabic and Indonesian (a comparative analysis)/ التعبير الاصطلاحي بين اللغة العربية واللغة الإندونيسية - Inayatul Fikriyah (UIN ANTASARI, 2022)
Idioms are one of the fields of study in semantics. Semantics is a branch of linguistics which studies the language meaning. This study is motivated by students who do not know the form of idioms used in learning. The aim of this study is to know the similarities and differences between Arabic and Indonesian idioms used in learning. The type of this study is library research using contrastive analysis method, which compared two languages in terms of meaning through a qualitative approach. The primary data were the Arabic Idiom Dictionary and a book entitled Indonesian Expression in contrastive anlysis of Arabic and Indonesian while the secondary data were taken from books and journals related to the study. And the results of this study, there are similarities between Arabic and Indonesian idioms terms of sentence form and meaning. There are differentces in Arabic idioms in terms of the intended meaning and differnces in Indonesian in terms of sentences the intended meaning. And there are other differences in terms of the vocabulary used.